A two-step parameter optimization algorithm for improving estimation of optical properties using spatial frequency domain imaging. (March 2018) - Hu, Dong; Lu, Renfu; Ying, Yibin
Highlights: An inverse algorithm for estimating optical properties from spatial frequency domain reflectance was optimized using Monte Carlo simulation. A two-step method based on the optimized inverse algorithm was proposed for parameter estimations. The two-step method was validated by experimental data. The optimized inverse algorithm results in better estimation of optical properties. Abstract: This research was aimed at optimizing the inverse algorithm for estimating the optical absorption ( μa ) and reduced scattering ( μs ′ ) coefficients from spatial frequency domain diffuse reflectance. Studies were first conducted to determine the optimal frequency resolution and start and end frequencies in terms of the reciprocal of mean free path (1/ mfp ′ ). The results showed that the optimal frequency resolution increased with μs ′ and remained stable when μs ′ was larger than 2 mm −1 . The optimal end frequency decreased from 0.3/ mfp ′ to 0.16/ mfp ′ with μs ′ ranging from 0.4 mm −1 to 3 mm −1, while the optimal start frequency remained at 0 mm −1 . A two-step parameter estimation method was proposed based on the optimized frequency parameters, which improved estimation accuracies by 37.5% and 9.8% for μa and μs ′, respectively, compared with the conventional one-step method. Experimental validations with seven liquid optical phantoms showed that the optimized algorithm resulted in the mean absolute errors of 15.4%, 7.6%, 5.0% for μa and 16.4%, 18.0%, 18.3% for μs ′ at the wavelengths of 675 nm, 700 nm, and 715 nm, respectively. Hence, implementation of the optimized parameter estimation method should be considered in order to improve the measurement of optical properties of biological materials when using spatial frequency domain imaging technique.